Role of forecasting support in decisionmaking process. The case of debt to equity conversion - Nita, Bartłomiej; Oleksyk, Piotr (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The articles addresses the usefulness of financial forecasting. Thus, the objective of the paper is to propose a forecasting approach that supports decision-making process in the context of debt to equity conversion. Methodology adopted in the paper involves an example case explaining the conversion of liabilities into equity. The considerations in the paper support the argument that the structured approach to financial forecasting is essential to understand the impact of debt to equity conversion on the future position of a company as reflected in its financial statement. The structure of the article is as follows. The first part of the paper focuses on the issues related to information support of decision-making process. The next section refers to financial forecasting in the context of debt analysis. In the last section we describe the use case, and the article concludes with a summary of work to date
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 474, s. 185-194
Keywords: financial forecasting; debt to equity conversion; prognozowanie finansowe; konwersja zobowiązań na kapitał własny